Matlab/simulink simulation of unified power quality conditioner-battery energy storage system supplied by PV-wind hybrid using fuzzy logic controller - Amirullah Amirullah; Ontoseno Penangsang; Adi Soeprijanto (Institute of Advanced Engineering and Science, 2019)
This paper presents performance analysis of Unified Power Quality Conditioner-Battery Energy Storage (UPQC-BES) system supplied by Photovoltaic (PV)-Wind Hybrid connected to three phase three wire (3P3W) of 380 volt (L-L) and 50 hertz distribution system. The performance of supply system is compared with two renewable energy (RE) sources i.e. PV and Wind, respectively. Fuzzy Logic Controller (FLC) is implemented to maintain DC voltage across the capacitor under disturbance scenarios of source and load as well as to compare the results with Proportional Intergral (PI) controller. There are six scenarios of disturbance i.e. (1) non-linear load (NL), (2) unbalance and nonlinear load (Unba-NL), (3) distortion supply and non-linear load (Dis-NL), (4) sag and non-linear load (Sag-NL), (5) swell and non-linear load (Swell-NL), and (6) interruption and non-linear load (Inter-NL). In disturbance scenario 1 to 5, implementation of FLC on UPQC-BES system supplied by three RE sources is able to obtain average THD of load voltage/source current slightly better than PI. Furthermore under scenario 6, FLC applied on UPQC-BES system supplied by three RE sources gives significantly better result of average THD of load voltage/source current than PI. This research is simulated using Matlab/Simulink.